IMPLEMENTASI SISTEM INFORMASI AKUNTANSI DI DALAM KEBERLANJUTAN UMKM DI INDONESIA - Nilawati, Yuana Jatu; Harahap, Cicely Delfina; Pakpahan, Arnolt Kristian; Chandra, Kristian (ISTEK WIDURI, 2025)
This study focuses on the implementation of Accounting Information Systems (AIS) and Information Technology (IT) in supporting the sustainability of advanced economic units. The objective of this research is to characterize economic units, examine the application of AIS, explain the effectiveness of AIS and IT within these units, and investigate the role of IT specialists. To achieve these objectives, a comprehensive analysis was conducted to understand the nature, structure, and operations of advanced economic units. This study explores how AIS is implemented and utilized in these units by examining the processes, procedures, and technologies involved in the collection, storage, processing, and reporting of both financial and non-financial data. In addition, this research evaluates the impact and effectiveness of AIS and IT on the overall performance and sustainability of economic units, highlighting both the benefits and challenges associated with the adoption and integration of these systems. The findings indicate that the effective implementation of AIS and IT has a positive impact on the performance of economic units, including improved decision-making capabilities, operational efficiency, and enhanced financial reporting. This study also provides valuable insights into the application of AIS and IT in advanced economic units and underscores the importance of these systems in ensuring sustainability. The findings of this research may serve as a guide for decision-makers and practitioners in optimizing the use of AIS and IT.